MR imaging of the brain in patients with diabetes insipidus. - Tien, R; Kucharczyk, J; Kucharczyk, W (American Journal of Neuroradiology, 1991)
Diabetes insipidus is a clinical syndrome characterized by the excretion of copious volumes of dilute urine combined with persistent intake of abnormally large quantities of fluid. There are two general forms of the disease, central (vasopressin deficient) and nephrogenic (vasopressin resistant). Diabetes insipidus of central origin most often results from lesions in the hypothalamic-neurohypophyseal axis. Twenty-six cases of central diabetes insipidus were evaluated with the use of high-field-strength MR imaging. A wide variety of precipitating conditions were found, including Langerhans cell histiocytosis, neoplasia, trauma, and infection. A thickened pituitary infundibulum was seen in most patients, and an absence of high intensity signal in the posterior pituitary lobe on T1-weighted images was seen in every case. Analysis of stalk morphology; associated brain findings; and correlation with the patient's age, sex, history, and radiographs of other body parts improved diagnostic specificity. When combined with clinical information, MR imaging is able to provide a specific diagnosis in almost all cases of central diabetes insipidus.